Phenotypic plasticity of growth ring traits in Pinus hartwegii at the ends of its elevational gradient - Carrillo-Arizmendi, Lizbeth; Vargas-Hernández, J. Jesús; Rozenberg, Philippe; Pérez-Suárez, Marlin; Martínez-Campos, Angel Roberto (Frontiers in Plant Science, 2023)
High mountain species have used phenotypic plasticity (PP) as a short-term mechanism that to modify their physiological traits in response to increasing temperatures over the past decades. The objective was to evaluate the response of P. hartwegii through its PP to temperature and precipitation at the ends of their elevational gradient on two volcanic mountains in central Mexico (La Malinche and Nevado de Toluca). Increment cores collected from 274 P. hartwegii trees were used to calculate their PP through reaction norms (RN) who relates the ring width and density variables with climate variables (temperature and precipitation). The sensitivity of trees (significant reaction norms RNS) to climatic variables was estimated, as well as the relative frequency of positively and negatively sloped RN (RNP and RNN, respectively). Likewise, the relationship between the PP value of the width and density variables was estimated through a correlation coefficient test. More than 70% of the individual trees showed significant RNs to temperature variables (Growing season (GST) and winter temperature (WMT)) for at least one growth ring variable, and there was a higher proportion of RNS at the lower end of the gradient on both mountains. There was an overall lower proportion of RNS for GST than for WMT. This was driven mostly by significant differences (P <0.05) between mountains and elevations for GST only. Variables related to ring width mostly had RNN, while those related to density tended to have RNP. The average PP was higher at the lower end of the gradient, especially on LM, both for the density variables and for the width variables, despite high intrapopulation variability on both mountains. The results indicate that P. hartwegii presents spatially differentiated plastic responses in the width and density of ring growth. PP was particularly strong at the lower elevations, which have the highest temperatures and aridity index, putting these populations at risk from the constant global warming driven by climate change.